Has COVID-19 changed the correlation between cryptocurrencies and stock markets? - Ines Abdelkafi; Youssra Ben Romdhane; Sahar Loukil (European Journal of Government and Economics (EJGE), 2023)
The COVID-19 pandemic has challenged the notion that cryptocurrencies are uncorrelated with traditional asset markets. This study uses VAR-OLS techniques to investigate the time-varying correlation between Bitcoin and three major European stock market indices from January 4, 2016, to February 26, 2021. Our results show that cryptocurrencies and stock markets are dependent during crisis periods, but not during non-crisis periods. This confirms the time-varying correlation between cryptocurrencies and stock markets, which depends on the extent and persistence of responses to own and cross shocks. To improve the robustness of our results, we also test the impact of government measures on Bitcoin and stock market indices and find that they are both affected by these measures. Our study adds to the literature by examining the impacts of pandemics on the correlations between Bitcoin returns and the stock market, oil, and gold index returns, which have so far been unaddressed.
Keywords: I1; D53; G15; G12; C22; 330; Bitcoin; COVID-19; financial markets; stock indices